Strategi Ketahanan Perusahaan untuk Memperjuangkan Berjalannya Bisnis Sehingga Terciptanya Ketahanan Negara - Mayangsari, Efriska Ginasti (Blantika: Multidisciplinary Journal, 2025)
This study explores corporate resilience strategies in sustaining business operations as a critical contribution to national resilience. Amid growing external pressures such as social conflict, economic instability, and environmental demands, companies must develop adaptive strategies that integrate effective communication and sustainable social responsibility practices. Using a mixed-methods approach, this explanatory research involved quantitative data collection through stakeholder questionnaires and qualitative data via in-depth interviews with CSR and general affairs staff. The findings reveal that corporate resilience is significantly influenced by a company’s ability to build reciprocal and transparent relationships with both internal and external stakeholders. Strategic implementation of Corporate Social Responsibility (CSR) programs not only mitigates conflict but also strengthens a company’s public legitimacy. Moreover, resilience strategies that include stakeholder engagement, proactive risk management, and organizational communication foster operational stability. These actions support national resilience by generating employment opportunities, promoting social welfare, and enhancing local economic development. The study emphasizes that CSR should not be viewed as a financial burden but as a long-term investment aligned with sustainable development goals. It is recommended that companies integrate CSR into core business strategies, strengthen public relations functions, and maintain participatory communication with all stakeholders. Ultimately, resilient companies play a vital role in fostering national strength, particularly in ensuring economic continuity and social harmony in times of uncertainty.